Efektivitas Filtrasi Multi-Media dalam Menyisihkan TSS dan COD dari Air Bekas Wudhu - Nur, Ansiha; Ruslinda, Yenni; Ananda, Dimas Rizki; Mardatillah, Regina (Jurnal Serambi Engineering, 2025)
This study aims to calculate the quantity of used wudhu wastewater at the Nurul Ilmi Mosque, Universitas Andalas, test the effectiveness of filtration in removing TSS and COD, and evaluate its potential use as non-potable water. Quantity measurements were carried out on Monday, Friday, and Sunday with triplicate tests. Filtration used a continuous PVC reactor (capacity 2.54 L) with an influent discharge of 2 gpm and 4 gpm. The filtration media consisted of activated carbon, zeolite sand, and silica sand. The results showed that the highest volume of used ablution water was on Friday at 35.865 ± 9.67 L/sec. TSS and COD removal at a discharge of 2 gpm and 4 gpm were 74.03% ± 2.98 and 76.19% ± 3.37, and 70.01% ± 2.98 and 70.01% ± 0.00, respectively. The 2 gpm discharge showed the best removal results, although the COD value did not meet the Quality Standards of PP No. 22 of 2021 (class 2). The t-test showed that the variation in discharge did not have a significant effect on the removal of TSS and COD (p>0.05). With its potential for utilization, it is recommended to extend the residence time at a discharge of 2 gpm so that COD meets the quality standards, so that used ablution water can be used as non-potable water.